Doctor’s Legal Liability Against Consultation Via Online if a Patient Experiences Loss - AdiTio Helga Ramanda; Anak Agung Gede Wahyu Parama Arka; Istanti Siti Rahmawati Hartiwi; Agus Yudha Hernoko (Institute of Medico-legal Publications Pvt Ltd, 2021)
Health is need of every human being in living his/her life. Health is also crucial because without good health, it will be difficult for every human being to carry out his/her daily activities. Entering an era of rapid development, the world is faced with the emergence of new technologies in the medical field that allow doctors to practice in a virtual space. To analyze the legal basis of online medical services as well as to analyze the legal liability of doctors in providing online medical services if a patient experiences loss. Until now, there have been no detailed regulations regarding online-based medical services, both in statutory provisions and in the provisions of the medical code of ethics. Law Number 36 of 2009 concerning Health and Law Number 29 of 2004 concerning Medical Practice so far have not been used as a reference for the administration of medical practice using online-based medical services. Furthermore, Law Number 11 of 2008 concerning Electronic Information and Transactions also cannot be used as a reference.